Construct a Tool for Aspect-Oriented Analysis and Design Based on Theme Approach - Nada Saleem; Mohammad Abdulwahab (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this research, a (RADC-AO) tool was constructed and implemented for the requirements analysis, design and stub-code generation according to aspect-oriented (AO) concepts based on theme approach. RADC-AO automatically identifies crosscutting concerns in natural language requirements text by using natural language processing (NLP), analyze requirements and apply a set of operations on themes got in the analysis process, design classes and aspects, draw class diagram, and generates stub-code. RADC-AO tested by input complete informal text requirements for payroll system (that contains security, logging, authorization, in addition to its core functionality which includes employees information entering, loans information entering, and payment calculation), RADC-AO successes in the test and gives good results.